Standardising Dementia Diagnosis Across Linguistic and Educational Diversity: Study Design of the Indian Council of Medical Research-Neurocognitive Tool Box (ICMR-NCTB). (12th December 2019) - Iyer, Gowri K.; Paplikar, Avanthi; Alladi, Suvarna; Dutt, Aparna; Sharma, Meenakshi; Mekala, Shailaja; Kaul, Subhash; Saroja, Aralikatte Onkarappa; Divyaraj, Gollahalli; Ellajosyula, Ratnavalli; Ghosh, Amitabha; Hooda, Roopa; et al.
Abstract: Objectives: While the burden of dementia is increasing in low- and middle-income countries, there is a low rate of diagnosis and paucity of research in these regions. A major challenge to study dementia is the limited availability of standardised diagnostic tools for use in populations with linguistic and educational diversity. The objectives of the study were to develop a standardised and comprehensive neurocognitive test battery to diagnose dementia and mild cognitive impairment (MCI) due to varied etiologies, across different languages and educational levels in India, to facilitate research efforts in diverse settings. Methods: A multidisciplinary expert group formed by Indian Council of Medical Research (ICMR) collaborated towards adapting and validating a neurocognitive test battery, that is, the ICMR Neurocognitive Tool Box (ICMR-NCTB) in five Indian languages (Hindi, Bengali, Telugu, Kannada, and Malayalam), for illiterates and literates, to standardise diagnosis of dementia and MCI in India. Results: Following a review of existing international and national efforts at standardising dementia diagnosis, the ICMR-NCTB was developed and adapted to the Indian setting of sociolinguistic diversity. The battery consisted of tests of cognition, behaviour, and functional activities. A uniform protocol for diagnosis of normal cognition, MCI, and dementia due to neurodegenerative diseases and stroke was followed in six centres. A systematic plan for validating the ICMR-NCTB and establishing cut-off values in a diverse multicentric cohort was developed. Conclusions: A key outcome was the development of a comprehensive diagnostic tool for diagnosis of dementia and MCI due to varied etiologies, in the diverse socio-demographic setting of India.